Knowledge, practice, and factors affecting peripheral intravenous catheters among nurses working in Dessie City public hospitals - Belachew Tegegne; Dawit Checkole; Mekuriaw Wuhib Shumye; Leul Mekonnen Zeru; Zemen Mengesha Yalew; Sewunet Ademe; Metadel Tegegne Shiferaw; Afework Edmealem (BMC Nursing)
Abstract Background Proper knowledge and practice are essential to prevent complications such as infection, phlebitis, and infiltration. Several factors—including training, workload, resource availability, and institutional protocols—may influence nurses’ knowledge and performance in PIVC care. However, few studies have examined nurses’ knowledge and practice regarding peripheral intravenous catheters. This study aimed to analyze the knowledge, practice, and factors influencing peripheral intravenous catheters among nurses working in Dessie City public hospitals. Methods An institution based cross-sectional study was carried out among 423 nurses between May 10 and May 30, 2024. Participants in the study were chosen using a simple random sampling technique. A standardized, self-administered questionnaire was used to gather data. Data was entered into Epidata version 4.6.1 and then exported to SPSS version 23 for analysis. Binary logistic regression and descriptive statistics were used. Variables with a 95% CI and a p-value of less than 0.05 were declared statistically significant in the multivariable analysis. Results Over half (56%) of nurses were females, and the mean (± SD) age was 29.8 (± 0.2) years. Majority (58.4%) of nurses had good knowledge. Age 20–29 years (AOR = 0.28, 95% CI: 0.12, 0.63, P = 0.002), surgical ward (AOR = 2.87, 95% CI: 1.66, 4.95, P = 0.001), females (AOR = 0.34, 95% CI: 0.22, 0.54, P = 0.0001), workload (AOR = 0.49, 95% CI: 0.27, 0.89, P = 0.021), and training (AOR = 1.54, 95% CI: 1.01, 2.49, P = 0.045) were factors of knowledge. Whereas, 51.5% of nurses had good practice. Age 30–39 years (AOR = 0.23, 95% CI: 0.09, 0.58, P = 0.002), Diploma (AOR = 4.85, 95% CI: 1.96, 11.98, P = 0.01), experience (AOR = 0.48, 95% CI: 0.25–0.9, P = 0.023), pediatric ward (AOR = 2.79, 95% CI: 1.07, 7.27, P = 0.036), workload (AOR = 2.24, 95% CI: 1.17, 4.3, P = 0.016), frequency of handling PIVC (AOR = 3.83, 95% CI: 1.15, 12.68, P = 0.028), and good knowledge (AOR = 4.97, 95% CI: 3.06, 8.06, P = 0.0001) were factors of practice. Conclusion The majority of participants had good knowledge and practice about peripheral intravenous catheters. The availability of antiseptic solution, sex, age, working unit, workload, and training were significantly associated with knowledge. Age, marital status, educational level, professional experience, working unit, existence of infection prevention guidelines, frequency of handling peripheral intravenous catheters, and having good knowledge were predictors of practice. Clinical trial number Not applicable.